(untitled) (Research, Society and Development, 2023)
The main objective of this research was to analyze the concepts of leadership and Quality of Life at Work (QWL) used by organizations in the process of implementing PQWT (Quality of Work Life Programs), as well as the possible associations between these two concepts. The expression QWL appeared in the specialized literature in the early 1950s, representing a search for models of studies that involved the individual, work and organization and, since then, has gained complexity, especially because it integrates the responsibility of generating well-being for workers. as well as organizational development in balance. This study is characterized by a qualitative, exploratory research, whose construction technique was the Integrative Literature Review, in the Periódicos CAPES, PePSIC, SciELO and Schoolar Google databases, from 2012 to 2022. The construction of the results and discussions was carried out from the reading of 22 texts that met the previously established inclusion criteria. The result also revealed little emphasis on the “leadership X QWL” relationship, which leads us to understand the need to carry out new studies that can contemplate the practice of QWL guided by the conception of leadership and strategic management of people in organizations.